Detection of freshwater mussels (Unionidae) using environmental DNA in riverine systems. Issue 3 (27th January 2020) - Gasparini, Louis; Crookes, Steve; Prosser, Ryan S.; Hanner, Robert
Abstract: Environmental DNA (eDNA) methods are being developed for use in conservation biology to improve upon conventional species survey techniques. Validation of eDNA methods in different environmental contexts is required if they are to be widely adopted. One potential application of eDNA methods is for the detection of freshwater mussels (Bivalvia: Unionidae), which are among the most imperiled species in North America. Conventional unionid survey methods are highly invasive and can be difficult to conduct due to issues with morphological identification and their cryptic use of habitat. eDNA methods can potentially provide a non‐invasive, extremely specific, and highly sensitive alternative. Here, we examine the effectiveness of eDNA methods at detecting an imperiled unionid, the wavy‐rayed lampmussel ( Lampsilis fasciola ), in lotic systems with moderate discharge. We developed a novel qPCR assay for the detection of L. fasciola eDNA, which included a custom internal positive control to check for PCR inhibition. We used different experimental densities of caged L. fasciola specimens as a point source of eDNA within two rivers of the Grand River watershed in Southern Ontario. Sampling occurred at set distances downstream of the cage using purpose‐built sampling equipment. Detection was obtained at the cage (i.e., point of eDNA shedding) but not downstream at distances ≥10 m during stream discharges of approximately 1, 632–2, 332 L/s. The results indicate that eDNA is diluted rapidly in rivers with moderate discharge and that high‐resolution spatial sampling efforts may be necessary to obtain meaningful eDNA‐based distribution data of unionids, and other sessile organisms, present at low density in lotic systems. Abstract : Herein we present the eDNA‐based detection of an imperilled species of unionid, Lampsilis fasciola, using caged molluscs as a point source of eDNA in riverine systems. In doing so we present results that indicate the directions that future eDNA surveys should take to increase sampling optimality and detection rates for unionids present at low density in lotic environments.